Changes in Weight, Sedentary Behaviour and Physical Activity during the School Year and Summer Vacation - Chiaki Tanaka (International Journal of Environmental Research and Public Health, 2018)
Background: To examine bidirectional associations between body weight and objectively assessed sedentary behaviour (SB) and physical activity (PA) during the school year and summer vacation. Methods: Participants were 209 Japanese boys and girls (9.0 ± 1.8 years at baseline). SB and PA were measured using triaxial accelerometry that discriminated between ambulatory and non-ambulatory PA, screen time measured by questionnaire during the school-term was evaluated in May and the summer vacation, and relative body weight measured in May and just after the end of summer vacation. Results: There were no significant relationships between changes in SB or PA and changes in body weight. However, higher relative body weight at baseline was associated with decreased non-ambulatory moderate PA (p = 0.049), but this association was slightly diminished after adjusting for change in SB (p = 0.056). Longer screen time at baseline was also associated with increased relative body weight (p = 0.033). Conclusions: The present study revealed that body weight might be particularly influential on non-ambulatory moderate PA while SB, PA or changes in these variables did not predict changes in body weight. Moreover, screen time during the school year is a predictor of change in relative body weight during the subsequent summer vacation.